Visual politics of the estado novo realized on the Alameda Dom Afonso Henriques in Lisbon – the construction of ideal citizenship? - Hartmann, Jakob (2016)
The stylistic categorization of the Estado Novo has been intensely discussed by Portuguese art historians. The square Alameda Dom Afonso Henriques in Lisbon (Alameda) can be seen as paradigmatic for the architecture of power of the Estado Novo. The Alameda forms a gardened valley between two hills. There you find two prominent and highly propagandist buildings: The Instituto Superior Técnico (IST) and the Fonte Luminosa are dedicated to modern sciences and respectively to the harmonious contribution of nature to the city. The iconography of the Alameda as well as its incorporation into the propagandist use of urban planning in the 1930s and 1940s exemplify the visual politics during Salazarism. Urban planning programs intended to create cities that would preserve the character of a traditional catholic society and at the same time answer to the need to modernize the country and evoke the image of a progressive state. Thus, public buildings and urban squares such as the Alameda contributed to design a corporate image and to the ‘spirit’ of the regime.